Analisis Tantangan dan Strategi Ketahanan Pangan di Indonesia - Rahakbauw, Isro' Kurniawan; Lindiasari Samputra, Palupi (JURNAL AGRICA, 2025)
The issues of rapid population growth, rapid urbanization, and the impact of the Covid-19 pandemic on the agricultural sector present significant challenges to food security and resilience in Indonesia. Focusing on food sovereignty, security, and resilience, this study reveals the complex problems faced by Indonesia. The results indicate that Indonesia is still struggling to ensure adequate food availability, adapt to climate change, and reduce hunger and malnutrition, especially among children. Despite progress in the category of food affordability, further efforts are needed in food technology research and development, as well as a strong political commitment to overcome existing regulatory challenges. Several strategies for achieving sustainable food security are proposed in this paper, including enhancing food biodiversity, supply chain management, increasing domestic food production, and improving farmers' incomes. However, obstacles remain in the market structure dominated by a small number of traders, which can affect food prices and accessibility for the community. Other challenges include increasing efficiency in food distribution, protecting natural resources, and sustainable approaches to land use in agriculture. By understanding the core challenges and opportunities for sustainability improvement, this study is expected to make a positive contribution to efforts to enhance food security and resilience in Indonesia, ensuring community welfare and inclusive and sustainable economic growth.